Socialization to Improve Reading, Writing, and Numeracy Literacy Skills at SMA Negeri 1 Poli Polia - Izharuddin Pagala; Widyah W; Sidan S; Junarty Iswari; Sinda Pratiwi; Nesa N; Rifka Aprilliyah; Muhamad Aljunanto; Alwin Kamarudin; Alvendra Kirana; Uwais Abdullah Muhyan (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
The socialization program to improve literacy skills in reading, writing, and arithmetic held at Poli Polia 1 Public High School aims to strengthen students' basic skills in reading comprehension, expressing ideas in writing, and applying arithmetic skills in everyday life. The activity was implemented using participatory methods such as discussions, educational activities, and experience-based learning. Based on the implementation results, there was an increase in students' interest and enthusiasm for learning basic literacy. On the other hand, teachers were also motivated to develop more creative learning strategies and support literacy improvement. Overall, this socialization activity plays an important role in building a culture of literacy at Poli Polia 1 Public High School.